Public debt through the ages - Eichengreen, Barry; El-Ganainy, Asmaa; Esteves, Rui Pedro; Mitchener, Kris James (Washington, DC, 2019)
"We consider public debt from a long-term historical perspective, showing how the purposes for which governments borrow have evolved over time. Periods when debt-to-GDP ratios rose explosively as a result of wars, depressions and financial crises also have a long history. Many of these episodes resulted in debt-management problems resolved through debasements and restructurings. Less widely appreciated are successful debt consolidation episodes, instances in which governments inheriting heavy debts ran primary surpluses for long periods in order to reduce those burdens to sustainable levels. We analyze the economic and political circumstances that made these successful debt consolidation episodes possible."